Estudio cinemático de los saltos ornamentales en trampolín: Una visión hacia lo corporal - Uribe, N. (Journal of Sport Pedagogy and Research, 2020)
This research consisted of analyzing the biomechanical characteristics involved in each phase of a series of ornamental jumps on the three-meter springboard. For this, video recordings were made of nine (9) male youth athletes who participated in the XVII Junior World Cup of Ornamental Jumping, Aachen, Germany. For the collection and analysis of the data in three dimensions, two Panasonic cameras were placed between 90 ° and 120 °. 21 anatomical points and two trampoline points were digitized. Subsequently, the kinematic variables were quantified and analyzed with the computerized motion analysis software "Hu-m-an" v. 5.0. It was concluded that the projection characteristics are fundamental for the achievement of the flight phase and entry into the water, obtaining results similar to those registered in international investigations. The projection angle average the 80°. Deficiencies were found in the flight phase to define and group the body, affecting aesthetics and body, in the same way at the time of entering the water an over-effort of the upper body was appreciated due to the passivity of the lower body, which caused an entry hyperextension leaving the lower limbs delayed and displacing water during entry.